Common Constructal Principles in Design of Transportation Networks in Plants and Animals - Kizilova, N. (My University, 2008)
Common principles of design of long-distance liquid transport in the nature are discussed. Some results of measurements on the preparations and casts of the large systemic and small and medium intraorgan arteries are presented. The regularities between the diameters and the branching angles of the arteries in the bifurcations are revealed. The results of measurements on the conducting systems of plant leaves with different shape, size and type of the vasculature are also presented and compared to the arterial vasculatures. It is found the principles of construction are the same in the transportation networks of animals and higher plants and correspond to the model of optimal branching pipeline that provides liquid delivery at minimal total energy costs. A relationship between the length of the path along any subtree of the pipeline and the corresponding drainage area has been found for the leaf venation. The relationship corresponds to the Hack’s law revealed for the river basins. A model of the steady flow in the pipeline with permeable walls is proposed for the liquid delivery in the leaves. It was found, a balance between the inflow of the liquid into a subtree and its consumption by the cells in the corresponding area leads to the Hack’s law. A comparative study of the hydraulic conductivity of the leaves of different evolutionary age is carried out and validity of the constructal law is shown.
Keywords: fluid transport networks; constructal principle; design and function; plant conducting systems; arterial systems; optimality